Phyllodiaptomus (Phyllodiaptomus) roietensis, a new diaptomid copepod (Copepoda, Calanoida) from temporary waters in Thailand and Cambodia, with a key to the species - Sanoamuang, La-orsri (Zookeys, 2020)
Abstract. Phyllodiaptomus (Phyllodiaptomus) roietensissp. nov. was collected from temporary water bodies in Roi Et and Nakhon Ratchasima provinces in northeastern Thailand and Kampong Thom Province in central Cambodia. The new species is closely related to Phyllodiaptomus (P.) surinensis Sanoamuang & Yindee, 2001 in that it shares common morphological characters in the males: urosomites 2–3, P5 intercoxal sclerite, right P5 Exp-2, and left P5 Exp. Minor differences on the right antennule, right caudal ramus, P5 basis and Enp exist. The females differ in their Pdg 5, genital double-somite, and P5. An updated key to the species of the genus Phyllodiaptomus Kiefer, 1936 is provided.